UPAYA NORWEGIA DALAM PENYELESAIAN KONFLIK ANTARA PEMERINTAH KOLOMBIA DENGAN FUERZAS ARMADAS REVOLUCIONARIAS DE COLOMBIA - EJÉRCITO DEL PUEBLO (FARC-EP) 2010-2016 - Kukuh Iqbal, (2022)
The conflict between the Colombian government and FARC-EP has been going on for a long time. Various efforts have been made by the Colombian government to end the conflict. In the end when President Juan Manuel Santos came to power in 2010, the Colombian government held talks with FARC-EP by inviting Norway and Cuba as a mediator. Norway was chosen because it was considered experienced and could be a mediator in helping to settle this conflict. The Norwegian experience in overcoming various conflicts in various parts of the world is needed by the Colombian and FARC-EP governments to guarantee them in the negotiation process. The role of Norway is needed in overcoming the conflict that has taken place for decades this year. This study aims to analyze Norwegian's efforts regarding conflict resolution in the resolution of the conflict between the Colombian government and FARC-EP. The efforts made by Norway finally managed to end the conflict between the Colombian governments with FARC-EP. This study uses qualitative methods and concepts of conflict resolution and mediation as analytical tools. In the end, the conflict between the Colombian government and FARC-EP ended with the signing of a peace agreement between the two parties in September 2016. Norway with the basis of 'Norwegian Model For Peace' by emphasizing neutrality, long-term commitment, trust and willingness to talk to any party managed to run His role as a guarantor state to create peace in Colombia.